Exploring the figured worlds of mindfulness and teaching. - Diamantis, Sophia; Graue, M. Elizabeth; Moss, Evan; Flook, Lisa (Anthropology & Education Quarterly, 2024)
In the high‐pressure world of education, mindfulness practices have been offered to help teachers and students to handle stress and manage their emotions. Here we describe how two fifth‐grade teachers experienced a mindfulness intervention, using the construct of figured worlds. We explore how they negotiated mindfulness in their practice, illustrating the power of an anthropological look at a typically psychological construct.